Qur'anic principles of tabligh communication and their relevance to interpersonal communication theory - Safrodin Safrodin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
This study discusses the gap between the normative communication principles of the Qur'an and modern interpersonal communication theory. Tabligh is a prophetic duty carried out by preachers to convey the message of Islam to humanity, both individually and collectively. This study is a qualitative literature review using thematic interpretation methods. Primary data were obtained by compiling Qur'anic verses related to the principles of tabligh, while secondary data consisted of various literature on interpersonal communication and da'wah studies. The data were analyzed using content analysis, examining the meaning of Qur'anic verses related to the principles of tabligh and communication. This study yielded the following findings. First, the Qur'an contains several principles of tabligh (Islamic teaching) and communication that are relevant to interpersonal communication theory, including qaulan husnan (good words), qaulan sadidan (true words), qaulan layyinan (gentle words), qaulan balighan (effective words), qaulan ma'rufan (good words), and qaulan kariman (noble words). This indicates that the Qur'an places honesty, empathy, politeness, kindness, and effectiveness as fundamental principles in conveying the message of Islamic propagation (tabligh). The concept of tabligh in the Qur'an thus reflects not only the activity of conveying Islamic teachings but also ethical and humanistic interpersonal communication practices. This study can contribute to the development of Islamic communication studies and strengthen the relevance of Qur'anic values ​​in the practice of tabligh and communication in society. ***** Studi ini membahas kesenjangan antara prinsip-prinsip komunikasi normatif dalam Al-Qur'an dan teori komunikasi interpersonal modern. Tabligh merupakan tugas kenabian yang dijalankan oleh para pendakwah untuk menyampaikan pesan Islam kepada umat manusia, baik secara individual maupun kolektif. Penelitian ini merupakan penelitian kualitatif dengan menggunakan studi kepustakaan dan metode tafsir tematik. Data primer diperoleh dengan menghimpun ayat-ayat Al-Qur'an yang berkaitan dengan prinsip-prinsip tabligh, sedangkan data sekunder terdiri atas berbagai literatur mengenai komunikasi interpersonal dan kajian dakwah. Data dianalisis menggunakan analisis isi dengan mengkaji makna ayat-ayat Al-Qur'an yang berkaitan dengan prinsip-prinsip tabligh dan komunikasi. Penelitian ini menghasilkan beberapa temuan. Pertama, Al-Qur'an memuat sejumlah prinsip tabligh (penyampaian ajaran Islam) dan komunikasi yang relevan dengan teori komunikasi interpersonal, meliputi qaulan husnan (perkataan yang baik), qaulan sadidan (perkataan yang benar), qaulan layyinan (perkataan yang lemah lembut), qaulan balighan (perkataan yang efektif), qaulan ma'rufan (perkataan yang baik), dan qaulan kariman (perkataan yang mulia). Hal ini menunjukkan bahwa Al-Qur'an menempatkan kejujuran, empati, kesantunan, kebaikan, dan efektivitas sebagai prinsip-prinsip fundamental dalam menyampaikan pesan tabligh. Dengan demikian, konsep tabligh dalam Al-Qur'an tidak hanya mencerminkan aktivitas penyampaian ajaran Islam, tetapi juga praktik komunikasi interpersonal yang etis dan humanis. Penelitian ini dapat memberikan kontribusi bagi pengembangan kajian komunikasi Islam serta memperkuat relevansi nilai-nilai Al-Qur'an dalam praktik tabligh dan komunikasi di masyarakat.